(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In a social media setting, it is critical to explore the constructs that drive consumers’ reactions toward advertisements as the lack of understanding of these factors may lead to misplaced advertising for marketers online. This study creates a multifaceted advertising model that assesses the effect of informativeness, entertainment, irritability, and credibility on the valuableness of social media advertising and how these factors influence consumers’ buying intentions. It adopted a covariance-based structural equation modelling approach where primary data was collected by administering questionnaires to a sample study of 364 selected participants, who were university students, employees, and entrepreneurs. The data gathered were analyzed using confirmatory factor analysis and structural equation modelling method were used to examine the correlation between the identified predictors and purchase intention while validating the model constructed. The results established that a strong correlation exists between the perceived value of informativeness and credibility of social media advertising and customer buying intention. The findings, while frowning that advertisements with overly entertaining content may irritate potential buyers, posited that perceived value is critical in the conversion of advertising engagement into purchase habit. The study significantly highlighted that perceived value is the key mediator in the proposed model with a very strong correlation that impacts consumers’ buying intention; that is, consumers who perceive value in the ads are far more likely to express their buying intention. The study recommended that advertisers should focus on making their social media ads more valuable to positively affect customer perceptions.